P347 Vedolizumab for primary sclerosing cholangitis associated with inflammatory bowel disease: A multicentre cohort study from the GETAID. (16th January 2018) - Caron, B; Peyrin-Biroulet, L; Nachury, M; Bouhnik, Y; Seksik, P; Bouguen, G; Caillo, L; Laharie, D; Carbonnel, F; Altwegg, R; Reenaers, C; Serrero, M; et al.
Abstract: Background: Whether vedolizumab is effective and safe as a treatment of primary sclerosing cholangitis (PSC) is unclear. Methods: We performed a retrospective observational study, collecting data from 22 tertiary centres in France and Belgium affiliated to the GETAID from January 2015 to June 2016, on all consecutive patients with IBD and associated PSC treated with vedolizumab for at least 30 weeks unless vedolizumab was discontinued for PSC-related complications. Patients were retrospectively evaluated until week 54. Routine laboratory test values including alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), γ-glutamyltransferase (GGT), total bilirubin, C-reactive protein (mg/l) and serum albumin (g/l) were analysed. Liver enzymes changes were given according to the upper limit of normal (ULN). The primary efficacy objective was a decrease of at least 50% in the serum ALP concentration from baseline to week 30. Results: A total of 56 patients (39 males; 21 with Crohn's disease (CD), 34 with ulcerative colitis (UC) and 1 with indeterminate IBD; median age at diagnosis of PSC 25.1 [18.0–35.3] years; median age at diagnosis of IBD 19.8 [16.4–32.5] years) were included in this study. At baseline, concomitant treatment included ursodeoxycholic acid in 47 (83.9%) patients, steroids in 28 (50.9%), and immunomodulators in 19 (33.9%). At baseline, ALP, ALT, AST, total bilirubin and GGT, CRP and serum albumin were 2.2 ± 2.9 ULN, 1.7 ± 2.0 ULN, 1.3 ± 1.1 ULN, 1.2 ± 2.0 ULN, 5.3 ± 9.0 ULN, 17.5 ± 23.8 mg/l and 36.6 ± 5.3 g/l, respectively. At week 30 and 54, the data of 54 and 33 patients could be analysed. A decrease of at least 50% in the serum ALP concentration from baseline to week 30 was achieved in only 4 (7.4%) patients at week 30 and 3 (9.1%) at week 54. No changes in other liver tests was observed at week 30 and 54 with the exception of a mild increase in ALP concentration at week 54 (+0.4 ± 1.0 ULN, p = 0.02) whereas the mean CRP level significantly decreased at week 54. Adverse events were reported in 12 (21.4%) patients, mostly consisting in incidental infections in 7 patients and incidental cases of digestive cancers in 5 patients (three cases of colorectal cancer between week 22 and week 30 and two cases of cholangiocarcinoma between week 2 and week 6). Conclusions: Although VDZ showed effectiveness in patients with active refractory IBD, it did not improve liver tests at weeks 30 and 54 in PSC patients. The safety profile was consistent with previous data reported in IBD patients without PSC. Five cases of digestive cancer occurred during the follow-up period confirming the need for a tight surveillance program of patients with concomitant IBD and PSC.